Why Eating Breakfast Is Important for Optimising Human Metabolism? - HR Farshchi; MA Taylor; IA Macdonald (Tehran University of Medical Sciences, 2005)
Breakfast consumption appears to have declined in the last decades and eating breakfast, especially cereal, is associated with a lower risk of obesity. Serum cholesterol concentration is reported to be lower in adults eating breakfast (EB) and higher among those not. No study, to our knowledge, has investigated the effect of skipping breakfast (SB) on various aspect of energy metabolism. Thus, this study evaluated the effect of EB or SB on adult energy, carbohydrate and lipid metabolism. 10 healthy women (BMI: 23.2, SD: 1.4) were recruited after giving informed consent. Each subject participated in a randomised crossover trial which encompassed two 14-day intervention periods; EB in one of them and SB in the other with a 2-wk wash out period between. In EB, subjects were asked to consume a pack of whole grain cereal (Kellogg's, UK, 45 g) with 200 ml semi-skimmed milk between 07:00-08:00 and eat a chocolate bar (Nestle, 48g.) at 10.30-11.00. Then, they consumed 4 further meals of similar content to usual in the rest of the day at predetermined times every day for 2 wk. In SB, subjects consumed the chocolate at 10.30-11.00, and then had the cereal and semi-skimmed milk at 12.00-12.30. Then, they consumed 4 further meals of similar content to usual as for EB. Subjects consumed their normal diet for a 2-wk washout period between the two intervention periods. Subjects recorded their food intake on 3 days during each intervention, and came to the laboratory after an overnight fast at the start and end of each intervention period and their weight and anthropometric variables were measured. Blood samples were taken for glucose, lipids and insulin before and for 3 hr after a test meal (milk shake containing 30 kJ/kg, 50% CHO). Resting metabolic rate (RMR) was measured by indirect calorimetry before and after the test meal. Repeated-measures ANOVA, and paired t.test were used for the statistical comparisons. SB was associated with higher fasting total (3.4±0.4 compared with 3.1±0.4 mmol/l after EB, P